Biosynthesis and profiling of single cell carotenoids of Phaf ia rhodozyma in waste-based cultivation media - Arif Nurkanto; Rini Handayani; Ismu Purnaningsih; Mia Kusmiati; Ninu Setianingrum; Mulyadi Mulyadi; Endang Kusdiyanti; Achmad Dinoto (Journal of Microbial Systematics and Biotechnology, 2021)
In order to investigate the feasibility of low-cost media for producing well- characterized single-cell carotenoid, the study on biosynthesis and profiling carotenoid in the yeast of Phaf ia rhodozyma was carried out. We have successfully identified the profiles of single-cell carotenoids of P. rhodozyma, which was cultivated in glucose-based medium (MG), molasses-based medium (MM), and coconut water-based medium (MC). Cells were separately cultured in those media under aerobic batch culture system to obtain the carotenoid profiles based on high performance liquid chromatography (HPLC) analysis. The results showed that medium composition strongly affects the profiles of P. rhodozyma carotenoids represented by ratio of astaxanthin and beta-carotene (ratio A/B). Astaxanthin was highly synthesized in cells cultivated in MG with ratio A/B as much of 20:1. On the other hand, MM and MC produced a lower ratio A/B than MG as much of 0.4:1 and 0.2:1, respectively. In addition, carotenoids profiles were detected more diverse when this yeast species was cultivated in two waste-based media. This study provided a basic physiological knowledge of P. rhodozyma cells for carotenoid biosynthesis using potential low cost cultivation m